Treatment and Management of Osteoporotic Fractures: A Nation‐wide Survey of 484 Senior Orthopaedists in China. Issue 4 (November 2016) - Man, Yi; Pan, Wei; Lu, Jin; Li, Sen‐yuan; Zhang, Pian; Guo, Jun‐zhe; Yu, Shu‐fang; Zhang, Bei; Xiao, En; Zhang, Chao; Zuo, Wei; Jin, He‐juan; et al.
Abstract : Objective: To investigate the treatment given to osteoporotic fracture patients by orthopaedists at major hospitals in China. Methods: A 25‐item quantitative questionnaire survey, categorized into five domains, including primary purpose of osteoporosis treatment, anti‐osteoporosis therapy, calcium and vitamin D supplement, monitoring of osteoporosis, and knowledge of osteoporosis treatment, was designed to elicit information on orthopaedists' views on the treatment of osteoporotic fracture. A pre‐survey test was conducted with a sample of 40 orthopaedic specialists to confirm the reliability and validity of the questionnaire. Each interview of the survey took approximately 15 min and did not directly involve any patients. The survey was conducted through face‐to‐face interviews at 119 tier 3 hospitals in 28 cities across Mainland China. Results: A total of 484 valid responses were received. Seven in ten respondents have ≥10 years of professional practice. While two‐thirds believed that osteoporosis treatment was to prevent fractures or re‐fractures, 95.0% agreed that anti‐osteoporosis medication should be administered to patients with a history of fragility fractures. Three in four would prescribe anti‐osteoporosis medication perioperatively. Of these, 79.0% regarded bisphosphonates as the first‐line drug. Approximately 86.0% of the 21–30 years cohort chose bisphosphonates compared to 71.4% for those with ≤10 years. More of the younger (≤10 years) cohort chose calcitonin compared to their older (21–30 years) colleagues (25.7% vs 11.6%). The most commonly prescribed daily dose is 800 IU for vitamin D supplements and 600 mg/day for calcium. Conclusions: Our respondents generally adhered to guidelines for the treatment and management of osteoporosis. A significant number had recommended lower dosages of vitamin D and calcium. Some differences exist between the younger cohort and their older colleagues in the prescription of pharmacological therapies. The criteria for initiating therapy should be more holistic and include other factors besides bone mineral density (BMD). Our results demonstrated that more comprehensive guidelines for osteoporosis management and a greater awareness of these guidelines by orthopaedists are needed to enable them to better manage their patients.